Synthesis of Some N-Alkylated and 1,2,4-Triazole, 1,3,4-Oxa-, Thiadiazoles Containing 1H-Pyrazolo[3,4-b]pyridine Derivatives - A. El-Essawy, Farag; I.M. Rady, Safaa (Asian Journal of Chemistry, 2011)
N-Furan-2-yl-methylidene-4,6-dimethyl-1H-pyrazolo[3,4-b]pyridin-3-amine was prepared and alkylated, with the appropriate halo-compounds, to afford N-alkylated products. The hydrazide formation was converted into the key intermediate thiosemicarbazide which undergo the cyclization reactions under acidic and basic conditions, to give 1,2,4-triazole, 1,3,4-oxa- and thiadiazole derivatives. Condensation of the hydrazide with monosaccharide aldoses gave the corresponding sugar hydrazones, which readily undergo the cyclization reaction, on treatment with acetic anhydride, to afford the oxadiazoline derivatves. The synthesized compounds have been characterized by spectral and elemental analysis.